High-fat diet and chronic stress aggravate adrenal function abnormality induced by prenatal caffeine exposure in male offspring rats. Issue 1 (December 2017) - He, Zheng; Lv, Feng; Ding, Yufeng; Huang, Hegui; Liu, Lian; Zhu, Chunyan; Lei, Youyin; Zhang, Li; Si, Cai; Wang, Hui
Abstract We previously demonstrated thatprenatal caffeine exposure (PCE) suppressed fetal adrenal steroidogenesis and resulted in developmental programming changes in offspring rats. However, whether these changes play a role in adrenal corticosterone synthesis under high-fat diet (HFD) and unpredictable chronic stress (UCS) remains unknown. In present study, rat model was established by PCE (120 mg/kg.d), and male offspring were provided normal diet or HFD after weaning. At postnatal week 21, several rats fed HFD were exposed to UCS for 3 weeks and sacrificed. The results showed that compared with the corresponding control group, the serum corticosterone levels and adrenal steroid synthetase expression of the PCE offspring without UCS were reduced. Moreover, the glucocorticoid (GC)-activation system was inhibited, and insulin-like growth factor 1 (IGF1) signaling pathway expression was increased. With UCS exposure in the PCE offspring, serum corticosterone levels and adrenal steroid synthetase expression were increased, the activity of GC-activation system was enhanced, and adrenal IGF1 signaling pathway expression was decreased. Based on these findings, PCE induced adrenal hypersensitivity in adult male offspring rats, as shown by the reduced corticosterone levels under HFD conditions but significantly enhanced corticosterone levels with UCS, in which GC-IGF1 axis programming alteration may play an important role.